WASTE REDUCTION IN BODY REPAIR & PAINT AREA TOYOTA NASMOCO RINGROAD WITH LEAN MANUFACTURING APPROACH (Journal of Technology and Operations Management, 2021)
Toyota Nasmoco Ringroad Surakarta is a branch dealer that provides sales services, general repairs, body repair & paint, and spare parts. In the vehicle repair process, waste was found in the form of defect. The percentage of defect occurring from January to March 2020 shows an average of 85.22%. This study aims to identify critical waste defect and determine the factors that cause critical waste defect to occur and provide recommendations for improvements in order to reduce the waste that occurs in the area of body repair & paint. Efforts to reduce waste defects are carried out with a lean manufacturing approach. The research was carried out in three stages. The first stage begins with conducting a field study to identify problems. In the second stage, defect data is collected, which will be processed using Pareto diagrams so that the type of defect occurs most frequently. Furthermore, in the third stage, data processing begins with the identification of 9 wastes. Then identify the factors that cause waste using the fishbone diagram and the 5W + 1H method. Furthermore, the selected critical waste is processed using FMEA to identify systems that have a risk of failure which is indicated by the number of RPNs from the value rating of severity, occurrence, and detection. Based on the highest number of RPNs occurred in the polishing and reassying sub-area of 210. Proposals for improvement were a box, poka-yoke, and Kamishibai designs. Therefore, it is hoped that the proposed repair method will reduce the risk of defect arising during the vehicle repair process.